1989
DOI: 10.1139/f89-133
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Prey Rank and Preference by Young Planktivores for Short-Term and Long-Term Ingestion Periods

Abstract: New b r k 14850, USA Confer# I. L., and L. M. O' Bryan. 1989. Changes in prey rank and preference by young planktivores for shortterm and long-term ingestion periods. Can. ). Fish. Aquat. Sei. 46: 1026-18132.Feeding by young planktivorous fishes (yellow perch, Perca fhveseens, rainbow trout, Oneorhydeeheds mykiss, and lake trout, Sa%veliwus narnaycush) was examined. Prey rank was determined by offering a swarm sf one prey type and observing ingestion rates. During the initial feeding burst, larger prey general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 10 publications
(1 reference statement)
4
21
0
Order By: Relevance
“…When fish increase in size, the size spectrum of ingested prey increases, probably an effect of less gape-size limitation (Miller et al, 1988;Schael et al, 1991). The present data show preferences for intermediate sized prey (mostly copepodite stage IV-V, 0.7-1.0 mm), which agrees with others studies on herring (Munk, 1992) and other planktivores (Bence and Murdoch, 1986;Confer and O'Bryan, 1989;Graham and Sprules, 1992). However, for adult herring, one of the largest zooplankton items in the Baltic, Limnocalanus spp.…”
Section: Effects Of Fish Size On Prey Selectivitysupporting
confidence: 90%
See 1 more Smart Citation
“…When fish increase in size, the size spectrum of ingested prey increases, probably an effect of less gape-size limitation (Miller et al, 1988;Schael et al, 1991). The present data show preferences for intermediate sized prey (mostly copepodite stage IV-V, 0.7-1.0 mm), which agrees with others studies on herring (Munk, 1992) and other planktivores (Bence and Murdoch, 1986;Confer and O'Bryan, 1989;Graham and Sprules, 1992). However, for adult herring, one of the largest zooplankton items in the Baltic, Limnocalanus spp.…”
Section: Effects Of Fish Size On Prey Selectivitysupporting
confidence: 90%
“…This variation in length of fish and prey influences the relationship between foraging selectivity and relative prey size as seen in other studies on clupeoids (Checkley, 1982;Cohan and Lough, 1983;Raid, 1985;Lankov, 1986;Wespestad and Moksness, 1989;Conway et al, 1991;Munk, 1992). In other planktivores prey size is also positively correlated with fish size (Mills et al, 1984;Bence and Murdoch, 1986;Confer and O'Bryan, 1989;Shael et al, 1991). When fish increase in size, the size spectrum of ingested prey increases, probably an effect of less gape-size limitation (Miller et al, 1988;Schael et al, 1991).…”
Section: Effects Of Fish Size On Prey Selectivitymentioning
confidence: 66%
“…However, field observations and laboratory experiments with perch, both European Perca fluviatilis (Furnass 1979;Rajasilta & Vuorinen 1983) and its close relative North American P. flavescens (Mitchill, 1814) (Mills et al 1987;Confer & O'Bryan 1989), have shown that under specific circumstances these fish have behaved differently from the general scheme of Daphnia preference and contrastingly have selected the evasive cyclopoid and even more evasive calanoid copepods. Perch have done so particularly in long time feeding experiments or at high prey densities, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…USA prey are preferentially consumed (Brooks & Dodson 1965, Werner & Hall 1974, while others have shown the reverse (Bence & Murdoch 1986, Walton et al 1992. Confer & O'Bryan (1989) demonstrated that size selectivities of planktivorous fish depend on whether feeding is averaged over short or long time periods. These widely varying results have led to a debate about whether 'preferences' represent active (Mittlebach 1981, Werner et al 1983 or passive (O'Brien et al 1976, Maiorana 1981) choices, and the reasons for differential prey vulnerabilities (Pastorok 1981, Dunbrack & Dill 1983, Greene 1983).…”
Section: Introductionmentioning
confidence: 99%